Pengaruh Perceived Ease of Use dan Experience shopping terhadap Intention to buy dengan Perceived Usefulness sebagai Variabel Mediasi - Nahas, Maria Liliana Seran; Mitang, Berno B.; Huda, Nurul; Manek, Aquidowaris (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2023)
This research aims to determine the influence of Perceived Ease of Use and Experience shopping on buying intention in the Indonesian KK Marketplace by adding Perceived Usefulness as a mediating variable. The research method used is quantitative with the SEM PLS approach. The measuring instrument used is a questionnaire, then the data is processed using the SmartPLS program. The results of this research show that Perceived Ease of Use and Experience shopping has no effect on intention to buy, Perceived Ease of Use and Experience shopping have a significant effect on Perceived Usefulness, and Perceived Usefulness can mediate Perceived Ease of Use and Experience shopping can mediate intention to buy.